Measuring The Role Of Communication, Career Development, Rewarding In Improving HR Perfomance - Zulaika, Siti; Dharta, Firdaus Yuni; Dharmawan, Donny; Setyarto, Dwiatmodjo Budi; Setiawan, Roy (International Journal of Artificial Intelligence Research, 2024)
The purpose of this study is to examine and evaluate how PT BPRS Dinar Ashri KC workers' performance is impacted by career development, communication, and rewards. Terra. With 35 employees, the sample strategy makes use of a census sampling approach. Data analysis was done with IBM SPSS version 22. The study's findings indicate that incentives, career development, and communication all have a big impact on workers' output. Simultaneously, PT personnel' performance is significantly impacted by career development, incentives, and communication. Dinar Ashri BPRS.